2008
DOI: 10.1080/10826080802240906
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Daughter and Father–Daughter Attachment of College Student ACOAs

Abstract: This 2005 study compared parent-child attachment in 89 American female Adult Children of Alcoholics (ACOAs) as compared to 201 non-ACOAs. Women attended a large university in the southeastern United States. Participants categorized as ACOA on the Children of Alcoholics Screen Test (CAST; Jones, 1983) reported significantly more negative affect and less support from their fathers as indicated on the Parental Attachment Questionnaire (Kenney, 1987). When results were examined by the gender of the alcohol-abusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Department of Health and Human Services, 2008). Among college students, recent studies have demonstrated that 25%–30% meet criteria for being an adult child of an alcoholic (e.g., Grant et al, 2004; Kelley et al,2007, 2008).…”
Section: Childhood Experiences In Acoasmentioning
confidence: 99%
See 1 more Smart Citation
“…Department of Health and Human Services, 2008). Among college students, recent studies have demonstrated that 25%–30% meet criteria for being an adult child of an alcoholic (e.g., Grant et al, 2004; Kelley et al,2007, 2008).…”
Section: Childhood Experiences In Acoasmentioning
confidence: 99%
“…It is estimated that 8.3 million children (approximately 11%) live with at least one parent who abuses or is dependent on alcohol or other substances (U.S. Department of Health and Human Services, 2008). Among college students, recent studies have demonstrated that 25%-30% meet criteria for being an adult child of an alcoholic (e.g., Grant et al, 2004;Kelley et al, 2007Kelley et al, , 2008.…”
mentioning
confidence: 99%
“…ACOAs have a greater risk of problematic alcohol consumption and engage in externalising behaviours (Goodwin et al, 1973;Windle et al, 1995), while female ACOAs tend to display more internalising symptoms (Hibbard, 1993;Hinz, 1990) and insecure attachments (Kelley et al, 2008), but with more mature and effective coping strategies than men (Drapkin et al, 2015).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Osobnym zagadnieniem, obszernie poruszanym w literaturze, jest kwestia obrazu rodzica uzależnionego od alkoholu quality of parent-child relationship: negative communication patterns and a lack of communication with child, weak family bonds, a lack of interests in activities performed by children and a lack of trust to parents as well as the factors regarding the role modelling (for example substance abuse by a parent) -whereby it is assumed that the factors connected with the relationship quality have a more serious impact (Habib et al, 2010;McKay et al, 2011;Spooner, 1999). A separate issue, extensively described in the literature, is a problem of the image of alcohol-dependent parent and their influence on the child's and adult child's functioning in various spheres of life (Gąsior, 2011;Grzegorzewska, 2013;Kelley et al, 2010Kelley et al, , 2008Kelley et al, , 2005Kroll, 2004). It is assumed that the psychopathological symptoms -including alcohol abuse -in the group of individuals having an alcoholdependent parent are not a determinist phenomenon, but only probabilistic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the negative events may be more severe for these individuals than to individuals with no family history of alcohol addiction -because of a higher probability of emotional unavailability of the parent (drinking and/or non-drinking), a lack of support or positive patterns in terms of family functioning (Cierpiałkowska and Grzegorzewska, 2016). Taking into account the small number of studies regarding the parental assessment in the group of the alcohol-dependent, the author decided to check in her own research whether the alcohol-dependent and non-dependent individuals differ in terms of retrospectively assessed mother's and father's attitudes as well as if the retrospectively oraz jego wpływu na funkcjonowanie dziecka i dorosłego dziecka w różnych obszarach życia (Gąsior, 2011;Grzegorzewska, 2013;Kelley et al, 2010Kelley et al, , 2008Kelley et al, , 2005Kroll, 2004). Uważa się, że symptomy psychopatologiczne -również nadużywanie alkoholu -w grupie osób mających uzależnionego rodzica nie są zjawiskiem deterministycznym, lecz probabilistycznym i że konieczne jest uwzględnianie złożonych związków między indywidualnością i zasobami jednostki a czynnikami ryzyka występującymi na poszczególnych etapach rozwoju (Grzegorzewska, 2011).…”
Section: Introductionunclassified